Developing an Instrument to Measure Autonomous Adaptive Capacity to Climate Change among Urban Households - Selm, Kathryn R.; Hess, George R.; Peterson, M. Nils; Beck, Scott M.; McHale, Melissa R. (Frontiers in Ecology and Evolution, 2018)
The capacity of households in urban environments to adapt and react to climate change can affect the resilience of the whole community, and instruments for systematically measuring that capacity are needed. We used Raleigh, NC as a case study to explore the dimensions of autonomous adaptive capacity of urban households and to create a scale and associated survey instrument to measure them. Our approach was guided by four capitals that support human livelihoods: social, human, physical, and financial. We surveyed 200 households in Raleigh, NC, and used a principal components analysis to test the scale and survey instrument. Results suggest the scale is a useful and concise tool. Three major dimensions were present among the scale items: financial capital, political awareness, and access to resources. Together, these three dimensions can be used to measure adaptive capacity among different households. These findings are supported by similar work illustrating the value of income inequality and political awareness as indicators of adaptive capacity. Our results also demonstrate that complex relationships among the livelihood capitals may confound our ability to measure financial, physical, and human capitals separately. This framework for assessing adaptive capacity of households, with further refinement and testing, may be used in urban areas to evaluate programs designed to impact resilience to climate change.